Shaping the Sciences of the Ancient and Medieval World
X, 581 p. 154 illus., 13 illus. in color.
Keywords: This book contributes to a worldwide history of textual criticism and critical editions of ancient scientific texts. It first looks at ancient editorial practices, and at their impact on modern editions. Contributions analyze how, through time, the perception of what a text was may have changed, and influenced how scholarly texts were made accessible. The second section looks at the historical, political and social contexts within which editions and translations of ancient scientific texts were produced. Finally, the last two parts examine the specificities of editions and translations that bore on scholarly documents. Not only is there a focus on how the elements specific to scientific texts—such as diagrams and numbers—were treated, but case studies analyzing the specific work carried out to edit mathematical and astronomical texts of the past are also offered to the reader. The scholarship displayed in this work lays the foundation for further studies on the history of critical editions and raises questions to those who make scholarly translations and critical editions today.